Islamic personality in medical imaging students: a knowledge, attitude, and practice study at International Islamic University Malaysia (IIUM) - Muhamad Ruzlan, Siti Maryam; Zainuddin, Zainul Ibrahim; A. Rahman, Nor Azlina (IIUM Press, International Islamic University Malaysia, 2018)
This study examined the knowledge, attitude, and practice of the International Islamic University Malaysia Medical Imaging students towards the applications of Islamic personality in Medical imaging. The study serves to fill the gap in knowledge pertaining to the Islamic personality in the field of Medical imaging. The findings, followed by in depth discussions highlighted the areas of strength and weakness of students pertaining to the depiction of Islamic personality in the practice. The findings revealed that the students’ understanding on the detailed applications of the Islamic personality in Medical imaging needs to be enhanced. Another important finding is that the students felt the need for specific guidelines on Islamic Personality Traits (IPT) applicable for Medical imaging practitioners to be drawn up. The formulation of the guidelines in the form of a conceptual framework, could pave the right direction towards the promotion, understanding and internalization of Islamic personality in the Medical imaging practice.